مقارنة تأثير بعض مضادات الأكريات(مضادات الكوكسيديا) المستخدمة في علائق دجاج اللحم (الفرُّوج) على كفاءته الإنتاجية - نيصافي, علي; جبلاوي, رفيق; الحامض, بيان (Latakia University Journal -Biological Sciences Series, 2017)
تم تقييم تأثير ثلاث مضادات كوكسيديا( موننسين، سالينومايسين، كلوبيدول) تستخدم كإضافات إلى علف دجاج اللحم على بعض المؤشرات الإنتاجية والصحية للفرُّوج، قسمت الصيصان بعمر يوم عشوائيا لخمس مجموعات (أ، ب ،ج، د ،ه ) وزنت صيصان كل مجموعة وأعطيت(ب، ج ،ـد) مضادات الكوكسيديا على التوالي( الموننسين ،السالينومايسين، الكلوبيدول) من اليوم الأول،و تمت العدوى التجريبية للمجموعات (ب ، ج ، د ، ه) بـ10000 كيسة بيضية معدية .و بقيت المجموعة أ كشاهد سلبي و المجموعة ه كشاهد ايجابي، ودرست المؤشرات التالية (متوسط كمية العلف الأسبوعية المستهلكة من قبل كل صوص في كل مجموعة ومتوسط الزيادة الوزنية الأسبوعية ومتوسط الاستهلاك الكلي للطير في كل مجموعة ومن ثم متوسط الوزن الكلي للطير في كل مجموعة وسجلت نسبة النفوق و نسبة تحويل العلف الأسبوعي و الكلي للطير . تم حساب عدد الكيسات البيضية في 1غرام من الفرشة لتحديد نسبة الإصابة وتم تحديد شدة الإصابة اعتمادا على الآفات التشريحية المسجلة. أظهرت النتائج أن المجموعة أ تفوقت على جميع المعاملات وبفروق معنوية(p<0.05) ، و من بين المعاملات المضاف لها مضادات الكوكسيديا تفوق الموننسين على المضادين الآخرين بفروق معنويةp<0.05)) ، و تراجع أداء الطيور المعاملة بالكلوبيدول وظهر أسوأ أداء في المجموعة)ه) أي الشاهد الإيجابي. Coccidiosis is one of the major parasitic diseases of poultry. The disease has a great economic impact in poultry productions partly due to resistance of the organisms to anticoccidial drugs. In this study, to compare the effects of coccidiostatic efficacy of three drugs.one day old chicks were randomly divided into five groups of number chicks in each. groups2,3and4 were fed diets supplemented with Monensin, Salinomycin and Clopidol respectivelygroups1and 5 were designed as negative and positive control, received no coccidiostat ,The chicks of groups2,3 and 4 were infected with 10,000 sporulated viable oocysts of Eimeria species at one-day age. Feed intake, body weight gain, feed conversion ratio( FCR) ,mortality, lesion scores, and oocyst count per gram of litter were evaluated weekly. The results revealed that The highest mean of body weight was related to negative control followed by chickens treated with Monensin, Salinomycin and Clopidol the last . The highest FCR and Feed intake was belonged to negative control followed by chickens treated with Monensin, Salinomycin and Clopidol. The coccidiostat treatment group had a significant (p<0.05) higher mortality and fecal oocyst than the negative control but lower than positive control Monensin proved that it has better control lesion scores, oocysts shedding than other anticoccidia.